HETEROSIS STUDIES FOR VARIOUS MORPHOLOGICAL TRAITS OF BASMATI RICE GERMPLASM UNDER WATER STRESS CONDITIONS - M. Ashfaq; M. S. Haider; A. S. Khan; S. U. Allah (Journal of Animal and Plant Sciences, 2013)
Experiment was conducted to study heterosis for different morphological traits i.e. productive tillers per plant, primary branches per panicle, seeds per panicle, seed weight per panicle, 1000 seed weight, yield per plant and seed length width ratio under different irrigated conditions with Randomized Complete Block Design (RCBD) at University of Agriculture Faisalabad in 2010Our results indicates that the maximum heterosis under water stress condition i.e. 80.53% was recorded in (Basmati-2000 x CB-40) for seeds per panicle followed by 44.58% in (Basmati-198 x CB-17) for productive tillers per plant, 16.12% in (Basmati-198 x CB-32) for 1000 seed weight, 12.06% in (CB-32 x CB-14) for yield per plant, 11.10% in (Basmati-198 x CB-42) for primary branches per panicle, 10.14% in (Basmati-2000 x Super Basmati) for seed weight per panicle and 8.64% in (Super Basmati x CB-14) for length width ratio. From Griffing analysis genotypes CB- 17, CB-42, Basmati-198 and Basmati-2000 were found good general combiners for various traits especially under water stress condition. Maximum specific combining ability was found in Basmati-198 × CB-17 for primary branches per panicle, Basmati-198 x CB-17 for productive tillers per plant and CB-32 x CB-14 for yield per plant. Some hybrids had good heterosis for specific traits such as productive tillers per plant, 1000 grain weight and yield per plant that can be used for the development of new hybrid rice varieties. it can be concluded that our recent germplasm has great potential that can be used for development of new varieties.
Keywords: Heterosis; Oryza sativa L; Yield traits; Water stress; combining ability and Genotypes